Leishmaniose visceral em São Luís: uma avaliação após a descontinuidade do programa de controle de zoonoses - NOGUEIRA, Ranielly Araujo (2018)
Visceral leishmaniasis (VL) is a chronic, neglected and tropical disease caused by protozoa of the genus Leishmania, which are transmitted by sand flies and can infect dogs, humans, foxes and marsupials. Visceral leishmaniasis is endemic in Brazil, which has the Northeast region with the highest concentration of cases. At São Luís, MA, this disease has been endemic since the 80s and even with the actions of control and prevention through the Zoonoses Control Center, the disease presents a high number of canine and humans cases. In the last years, the frequency of disease control and prevention activities was minimal, which instigated the realization of this research, whose aim is to evaluate cases of visceral leishmaniasis in humans, reported between 2007 to 2016, and canines, after a discontinuation of actions and public policies under the responsibility of CCZ in São Luís, MA. Canine seroprevalence was determined by a sample survey, held in neighborhoods of the District Tirirical, in which the clinical profile and the serology of the participating dogs were analyzed. The evaluation of the reported cases of human VL was performed through data provided by the Municipal Health Secretary (SEMUS) of the municipality. The sample survey analyzed 190 domiciled dogs, both genders, with and without defined breed and age from six months. In the clinical analyzes, animals with clinical signs suggestive of infection, such as cachexia, skin lesion, nail enlargement, lymphadenopathy and ocular lesions were found in all neighborhoods. The frequency of seropositive dogs for LV was 45,8%, corresponding to 87 animals from these localities, of which 54% were asymptomatic, with little or no suggestive signs of infection. The analysis of human cases of VL, reported between the years 2007 to 2016, showed a total of 415 cases reported to SEMUS. Of these 415 cases, 64.6% (268/415) were notified in 2013, where it is possible to observe the increasing incidence of zoonoses, in the year which the Zoonoses Control Center (CCZ) stopped its control activities and prevention of disease. The Tirirical District, the site of the canine sample survey, represents a site of high concentration of human cases and dogs parasitized over the years, which is extremely worrying for a city of São Luís, since this district presents a large number of positive and asymptomatic dogs, functioning as silent reservoirs and responsible for maintaining the cycle. With these data, it is evident that there was an increase in human cases, possibly ratified by CCZ stoppage and that there are also a large number of parasited dogs in the analyzed District. In addition, the need for improvements in disease control and prevention strategies is evident so that the reduction of VL cases can occur in the municipality under study.